A Multidisciplinary Enhanced Recovery Programme Allows Discharge within Two days of Total Hip Replacement; Three- to Five-Year Results of 100 Patients. Issue 2 (March 2014) - Dawson-Bowling, Sebastian J.; Jha, Shilpa; Chettiar, Krissen K.; East, Debra J.; Gould, Gerard C.; Apthorp, Hugh D.
We present three- to five- year results of 100 sequential patients undergoing total hip replacement (THR) through a multidisciplinary rapid recovery programme, with mean length of stay (LOS) 1.99 nights. Patients attend pre-admission 'bone school', with talks and assessments by the senior sister, physiotherapist and occupational therapist. All receive an uncemented Corail-Pinnacle THR via piriformis-sparing mini-posterior approach. 'Low dose' spinal plus light general anaesthesia provides sensory block whilst retaining motor function; painfree mobilisation is predictably achieved within four hours. Following radiograph and haemoglobin check next morning, patients are discharged on meeting specific nursing/physiotherapy criteria. Those within 20 miles receive outreach follow-up. Follow-up assessment is undertaken using SF36, Visual Analogue, Merle d'Aubigné-Postel and Oxford Hip Scores. Mean age was 65 years (25-91), mean BMI 28.7 (19-43). ASA ranged 1-3 (mode 2), Charlson comorbidity index from 0-9 (mode 3). Major complications were: one dislocation with deep infection; one myocardial infarction; one trochanteric bursitis requiring exploration; one ceramic fracture; and three metal debris reactions. Several more minor complications occurred. LOS was longer in older patients (p = 0.03) and those with higher Charlson index (p = 0.02). Eighty-two patients remain under follow-up, (mean 37.8 months, range 36-61). Six have died; five underwent revision; seven have moved away or been lost. Ninety-seven percent remain quite or very satisfied. Our LOS is amongst the shortest in the United Kingdom, with encouraging outcomes. The SSP succeeds by involving all team-members, and managing patient expectation. At a time of limited healthcare resources we propose that our SSP could readily be reproduced elsewhere with similar benefits.